A flexible human detection service suitable for Intelligent Spaces based on a multi-camera network. (March 2018) - Almonfrey, Douglas; do Carmo, Alexandre Pereira; de Queiroz, Felippe Mendonça; Picoreti, Rodolfo; Vassallo, Raquel Frizera; Salles, Evandro Ottoni Teatini
The research field of the Intelligent Spaces has experienced increasing attention in the last decade. As an instance of the ubiquitous computing paradigm, the general idea is to extract information from the ambient and use it to interact and provide services to the actors present in the environment. The sensory analysis is mandatory in this area and humans are usually the principal actors involved. In this sense, we propose a human detector to be used in an Intelligent Space based on a multi-camera network. Our human detector is implemented in the same paradigm of our Intelligent Space. As a contribution of the present work, the human detector is designed to be a service that is scalable, reliable and parallelizable. It is also a concern of our service to be flexible, less structured as possible, attending different Intelligent Space applications and services, as well as their requirements. As it can be found in different everyday environments, a multi-camera system is used to overcome some difficulties traditionally faced by existing human detection approaches. To validate our approach, we implement three different applications that are proof of concept of many day-to-day real tasks. Two of these applications involve human–robot interaction. With respect to time and detection performance requirements, our human detection service has proved to be suitable for interacting with the other services of our Intelligent Space, in order to successfully complete the tasks of each application.